Mechanical properties of joints in 5052 aluminum made with adhesive bonding and mechanical fasteners. (June 2018) - Ufferman, B.; Abke, T.; Barker, M.; Vivek, A.; Daehn, Glenn S.
Abstract: In this work, the mechanical properties of joints made with a ridged tack only, one-part heat-curing epoxy only, and a combination of the two were evaluated. All samples were constructed using 1.6 mm thick 5052 aluminum. Testing was performed in lap shear, cross tension, and at 45°. A set of tests was also performed to investigate the mechanical strength of joints in lap shear under various surface preparation methods. It was found that the peak failure load was governed solely by the adhesive in hybrid joints. The performance gain from the inclusion of the ridged tack was greater energy absorption. The absorbed energy for a hybrid joint in lap shear configuration is closely approximated by the sum of energy absorbed with adhesive only and ridged tack only. The effect was much less pronounced for samples in cross tension and at 45°. Additionally, the adhesive strength was found to be completely unaffected by the surface preparation of the samples.